Cronartium flaccidum sporulates on new Euphrasia species in natural habitats in Finland - Kaitera, Juha; Kalleinen, L.; Mikkilä, J.; Hantula, Jarkko (Forest Pathology)
Natural sporulation of a pine stem rust, Cronartium flaccidum, was investigated in forested habitats in northern Finland. First, a diffuse sample (100) of seven species of hemiparasitic plants was collected in their natural habitats close to one another. C.flaccidum was found to sporulate on six species. The rust was most common on Melampyrum sylvaticum with 21% of the plants and 2% of the leaves carrying telia. Telia occurred occasionally also on Euphrasia frigida, E.nemorosa, E.stricta, Pedicularis palustris ssp. palustris and Melampyrum pratense (less than 5% of the plants and 0.3% of the leaves). The rust was absent on Rhinanthus minor. Second, a diffuse sample of each of M.sylvaticum, M.pratense, Euphrasia sp. and Rhinanthus sp. was collected from 10 sample plots surrounding the city area. C.flaccidum occurred on 0.29% of the leaves of M.sylvaticum, and 0.02%-0.03% of M.pratense and Euphrasia, but it was lacking from Rhinanthus. The results indicated that C.flaccidum was most common and widespread on M.sylvaticum, but sporulated sporadically also on Euphrasia sp., P.palustris and M.pratense. This is the first report of sporulation of C.flaccidum on Euphrasia frigida and E.nemorosa in their natural habitats. In contrast, a second rust observed in this survey, Coleosporium sp. needle rust, was much more common than C.flaccidum on the investigated plants. In the first site, 43%-54% of plants and 8%-17% of leaves of Melampyrum spp. and 0%-13% of plants and 0%-2% of leaves of Euphrasia spp., Rhinanthus minor and Pedicularis palustris carried uredinia or telia. In the second site, 9%-15% of leaves of Melampyrum spp. and 1%-2% of Euphrasia sp. and Rhinanthus sp. carried rust uredinia and/or telia. The results indicate frequent spore dispersal of both Cronartium and Coleosporium in the area, and versatile rust sporulation on hemiparasitic plant species. 2017